Формування механізму управління конкурентоздатністю підприємств - Очеретько, Лариса Михайлівна (My University, 2004)
Дисертація присвячена розробці науково обгрунтованих методичних і практичних рекомендацій з формування механізму управління конкурентоздатністю підприємств. Удосконалено теоретичні основи механізму управління конкурентоздатністю підприємств. Досліджено фактори, що забезпечують формування ефективної конкурентоздатності підприємств швейної галузі промисловості в ринкових умовах. The dissertation is devoted to development of the scientifically-proved methodical and practical recommendations on formation of the mechanism management of competitiveness of the enterprises. Theoretical bases of the mechanism of management are advanced by competitiveness of the enterprises. Factors which provide formation of effective competitiveness of the enterprises of a sewing industry in market conditions are investigated.
Keywords: ефективність; класифікація; конкурентоздатність; механізм управління; підприємства; формування; efficiency; classification; competitiveness; mechanism of management; enterprise; formation